SUSTAINABILITY THROUGH RESOURCE RECYCLING, SOIL FERTILITY AND CARBON SEQUESTRATION FROM INTEGRATED FARMING SYSTEMS IN WEST COAST INDIA - B. L. MANJUNATH; V. PARAMESH; G. R. MAHAJAN (The Bioscan, 2024)
A lowland integrated farming system model was studied for the productivity, profitability, inter-dependency and sustainability in West coast of India for four years. The model included rice based cropping systems (0.4 ha) viz., rice-cowpea, rice-groundnut, rice-brinjal and rice-sweet corn integrated with dairy and forage crops grown on the bunds of the field. The results indicated that rice-sweet corn + dairy was productive (32.6 t ha-1) and profitable system while rice-brinjal + dairy generated higher employment (256 man-days year-1) throughout the year. Dairy was found economical due to on-farm generated green fodder (6.7 tonne) throughout the year and efficient use of crop by-products, about 30-35% of the gross return contributed from the dairy except during 2014-15. The lowland farming system facilitated maximum recycling of nutrients through composting, on an average 101.2 kg of N integrated, 18.2 kg of P and 61.9 kg of K were recycled every year. Significantly higher carbon sequestration was noticed in rice-groundnut system (28.6 Mg C ha-1). The study concluded that integrated farming system including cereals, pulses, oilseeds and vegetables integration with dairy were productive, sustainable and economically viable for west coast region of India.